Fe3O4 nano-particles prepared by co-precipitation method using local sands as a raw material and their application for humic acid removal. Issue 1 (2nd January 2016) - Zulfikar, M. A.; Suri, F. I.; Rusnadi,; Setiyanto, H.; Mufti, N.; Ledyastuti, M.; Wahyuningrum, D.
Abstract : Magnetic Fe3 O4 nano-particles were prepared successfully from commonplace sands as a raw material. The nano-particles were synthesized by chemical co-precipitation of high purity iron separated from commonplace sands through acidic leaching. The characterization of the synthesized nano-particles was performed using X-ray diffraction, fourier transform infrared, scanning electron microscopy, transmission electron microscopy, and potential zeta. Finally, the nano-particles were used for adsorption of humic acid (HA) from aqueous solutions using batch adsorption technique. The effects of pH, adsorbent dosage, agitation time, initial HA concentration, and temperatures on HA adsorption were evaluated. The adsorption of HA onto nano-particles followed the Sips isotherm and pseudo-second order kinetics models. Thermodynamic parameters data indicated that the HA adsorption process was non-spontaneous and endothermic under the experimental conditions. The adsorption of HA from peat water (the real sample) using the nano-particles demonstrated that they were an adsorbent with great potential for the removal of HA from peat water.